Emerging leptospirosis in urban Sydney dogs: a case series (2017–2020). Issue 5 (25th January 2022) - Griebsch, C; Kirkwood, N; Ward, MP; So, W; Weerakoon, L; Donahoe, S; Norris, JM
Abstract : Canine leptospirosis has not been reported in the Sydney dog population since 1976. However, between 2017 and 2020, leptospirosis was confirmed in 17 dogs, five of which were known to hunt rodents. Dogs infected between 2017 and 2019 lived within a 3 km radius in the Inner City of Sydney (n = 11). In 2020, cases emerged across a broader area of Sydney; Inner City (n = 1), Inner West (n = 3), Lower North Shore (n = 1) and Upper North Shore (n = 1). The disease was characterised by severe hepatorenal involvement resulting in an unusually high case fatality rate (88%). In conjunction with supportive clinical signs, diagnosis was confirmed by real‐time PCR on whole blood (n = 1), kidney (n = 1), urine (n = 4), whole blood and urine (n = 9) or by seroconversion (n = 3). Antibody titres determined by Microscopic Agglutination Test (MAT) to Leptospira serovars were measured in 12 dogs: seven were positive for serovar Copenhageni, one was positive for serovar Hardjo, three were negative for all serovars, likely due to insufficient time for seroconversion before death and one had a low positive titre (1/50) for serovars Australis and Robinsoni. This sudden emergence of a highly fatal disease in pet dogs in Sydney has led to the introduction of Leptospira vaccination protocols for dogs living in inner Sydney using a monovalent vaccine containing serovar Copenhageni. The success of this vaccination program will require ongoing research to understand the emergence of leptospirosis in this region and the serovars involved.